Gottes Werk und Teufels Wirken: Traum, Vision, Imagination in der frühbyzantinischen monastischen Literatur - Krönung, Bettina (Millennium-Studien / Millennium Studies, 2014)
The volume provides the first comprehensive presentation of imaginary phenomena such as dreams and visions in early Byzantine monastic literature. Drawing on a broad range of sources, it examines imaginary experiences according to their literary expression and the cultural historical background they reflect, thus offering profound insights into the diverse treatment of imaginary phenomena in monastic literature